Development of Alloanti-Jka in a Patient with Hemolytic Anemia Due to Autoanti-Jkb. Issue 5 (21st January 2016) - Grishaber, Judy E.; Cordle, Delores G.; Strauss, Ronald G.
Abstract : Autoanti-Jk b and a transient autoanti-E were identified in a patient with autoimmune hemolytic anemia, and red blood cells negative for Jk b and E antigens were transfused. Twelve weeks after transfusion, the autoantibody appeared to have developed broad specificity. However, autoadsorption studies revealed that the broad reactivity was due to the development of alloanti-Jk a in addition to the autoanti-Jk b . Distinguishing this combination of alloanti-Jk a plus autoanti-Jk b from an autoantibody with broad specificity will be important in selecting Jk a antigen-negative red cells for subsequent transfusions. This case emphasizes the importance of additional serologic testing to detect alloantibodies in patients with broadly reactive warm autoantibodies.